THE EFFECTIVENESS OF PSYCHOPHARMACOLOGICAL INTERVENTIONS FOR SCHIZOPHRENIA - Mohammed Atallah Almasoudi, Bahegah Abdallah Alqubali, Jubran Zakri Shanya, Ahmed Abdullah Hassan Alqarni, Hadi Ahmed Hozam Almobarki, Yousef Hayyan Alruwaily, Saleh Mater Alosaimi, Ibrahim Mohammed Alfoud, ,; Sultan Ali Alharthi, Mohammed Eid Alenazi, Abdulhameed Jafar Mohammed Al Nahab, Fatima Ali Hawzan, Abdullah Shaya Al Dossari, Raed Saud Alduraywish, (Chelonian Research Foundation, 2022)
Antipsychotic polypharmacy continues to be common and is likely on the rise for the treatment of schizophrenia in actual clinical environments. Existing research indicates that antipsychotic polypharmacy may provide some therapeutic advantages. For instance, combining clozapine with another antipsychotic can lead to improved symptom management. Additionally, using aripiprazole with other medications might help reverse metabolic side-effects. However, it is important to interpret the results in the literature cautiously because to the limited number of high-quality research and the possibility of significant adverse effects. Furthermore, despite the limited amount of data currently available, two smaller-scale clinical studies provide first indications that transitioning from antipsychotic polypharmacy to monotherapy may be a realistic and sensible therapeutic choice. Multiple research have investigated methods to modify the prescription practices of doctors regarding the use of multiple antipsychotic medications. These findings indicate that educational programs alone may have little impact, but more assertive measures such as directly informing doctors via letters or phone calls may be more successful in lowering the use of multiple antipsychotic medications. Antipsychotic polypharmacy may be effective for some challenging clinical circumstances, but it should be used sparingly and might potentially be avoided in a significant number of patients. The lack of evidence highlights the need for more research on both the benefits and drawbacks of antipsychotic polypharmacy, as well as the effectiveness of interventions in existing polypharmacy treatment plans. Keywords: Additional therapy, supplementary therapy, medication for treating psychosis, combination therapy, mental disorder.